TOWARD A FUGITIVE ANTHROPOLOGY: Gender, Race, and Violence in the Field - BERRY, MAYA J.; ARGÜELLES, CLAUDIA CHÁVEZ; CORDIS, SHANYA; IHMOUD, SARAH; ESTRADA, ELIZABETH VELÁSQUEZ (Cultural anthropology, 2017)
In this essay, we point to the ways in which activist research methodologies have been complicit with the dominant logics of traditional research methods, including notions of fieldwork as a masculinist rite of passage. Paradoxically, while activist research narrates the experiences of violence enacted on racialized, gendered (queer and gendernonconforming) bodies, the complexities of doing anthropology with those same bodies have tended to be erased in the politics of the research. Thus, our analysis is twofold: we reaffirm activist anthropology’s critiques against the putatively objective character of the discipline, which effaces questions of race, gender, and class in the research process and asserts a neutral stance that replicates colonial and extractivist forms of knowledge production. At the same time, we critically examine how activist research replicates that which it critiques by not addressing the racialized, gendered researcher’s embodied experience and by presuming that rapport or intimacy with those with whom we are aligned necessarily results in more horizontal power relations. Drawing on fieldwork in El Salvador, Cuba, Palestine, Mexico, and Guyana, we examine how our gendered racial positionalities inflect the research process and consider how we can push activist methods to be accountable to the embodied aspects of conducting research in conflict zones, colonial contexts, and/or conditions of gendered and racialized terror. Ultimately, we call for a fugitive anthropology, a methodological praxis that centers an embodied feminist ethos, advancing the path toward decolonizing anthropology.